Mempertimbangkan Tingkat Maqasid asy-Syari’ah dalam Penentuan Anggaran Belanja Pemerintah (Evaluasi terhadap APBN 2008-2013) - Maftukhatusolikhah Maftukhatusolikhah (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2015)
The result of a study evaluating three things, namely: how to position maqasid ash-Shari'ah in the perspective of Islamic economy, how to determine the state budget according to the perspective of maqasid ash-Shari'ah, and how to distribute the state budget based on the perspective of maqasid ash-Shari'ah. It can be concluded that at first the state budget should be based on five aspects: the maintenance of religion, life, lineage, sense and treasure. Second, according to maqasid ash-Shari'ah by using domain analysis and looking at the realization of state budget in 2008–2013, the budget did not describe the level of the existing maqasid ash-Shari'ah or in the moderate level. It can be seen from the hierarchy pooling of maqasid ash-Shari'ah that the maintainance of life (hifdzu an-nafs) ranks first with a total budget of Rp. 137.4 trillion; followed by the maintenance of treasure (hifdzu al-mal) with a total budget of 122.9 trillion; maintenance of sense (hifdzu al-aql) with a total budget of 121 trillion; maintenance of religion (hifdzu ad-din) with a total budget of 40.6 trillion; and maintenance of lineage (hifdzu an-nasl) with a total budget of 12.4 trillion.